Services for Enhancing Elementary School Teachers’ Competence in Conducting Developmental Research Oriented toward the Quality of Learning - I Wayan Karta; Darmiany; Hari Witono; Wiwin Quranita (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2026)
The results of observations on elementary school teachers’ ability to plan and implement developmental research indicate that these competencies remain very low, particularly in terms of conceptual mastery and the preparation of developmental research plans. This condition is further supported by previous studies reporting that continuing professional development activities are still very weak in the area of scientific research. The objective of this community service program (PKM) was to improve elementary school teachers’ mastery of developmental research concepts and their skills in preparing developmental research plans in the city of Mataram. The methods applied included: (1) case-based learning to instil concepts and theories of developmental research; (2) workshop methods to enhance scientific attitudes; and (3) project-based activities to develop skills in preparing developmental research plans. The target participants consisted of 20 teachers representing elementary schools in the city of Mataram. The outcomes of the PKM activities were evaluated using observation techniques, including observations of improvements in conceptual and theoretical mastery and assessments of the proposal products of developmental research. The results of the PKM showed: (1) an increase in the average percentage of knowledge mastery from 64.65% before the PKM activities to 81.55% after the activities; (2) an improvement in scientific attitudes from an average of 65.90% before the workshop to 82.95% after the workshop; and (3) an increase in skills in preparing developmental research plans from an average of 65.85% before the project-based proposal development activities to 82.20% after the activities. It can be concluded that the PKM activities were effective in improving knowledge, scientific attitudes, and skills in preparing developmental research proposals oriented toward the quality of learning among elementary school teachers in the city of Mataram. It is expected that the participants will implement and disseminate the outcomes of this PKM to teachers in their respective schools.